Counsultation on the use of Chatgpt in Improving Digital Literacy in Rural Communities in Indonesia: Penelitian - Rizal Perlambang CNAWP; Smita Catur Sudyantara; Arifhan Ady Dj; Eka Sriwahyuni; Randi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The author conducted outreach for approximately twelve days in the villages of Ambulu, Bubun Batu, and Karang Agung, South Bengkulu. The four materials I explained at the beginning, before the two-way discussion, I hope the consultation participants will fully absorb them. Ultimately, I hope the use of GPT Chat in rural communities will improve their well-being. This includes workers who can improve their skills and thus increase their income, entrepreneurs who can increase their revenue, and even those who are unemployed who can improve their skills to find work or start a business. The author expresses his deepest gratitude to all those who contributed to the successful implementation of the consultation activities with rural communities throughout Indonesia, which are more specifically explained in the methods section. This article summarizes the findings of these consultations. The author sincerely hopes that these consultations will be beneficial in improving the welfare of rural communities.